Pain perception in 4–6-year-old children following intraoral dental injection with 26 and 31-gauge needles: a randomized controlled trial - N, Sneharaj; Sharma, Akhilesh; Siddaiah, Madhusudhan Kempaiah; Subramaniam, Priya (Journal of dental anesthesia and pain medicine: JDAPM, 2024)
Administering anesthesia in dentistry can be distressing for patients, especially those with dental fear and anxiety. Needle pain during local anesthesia is a common concern in intraoral procedures. This study aimed to compare pain perception in 4-6-year-old children following intraoral dental injections with 26- and 31-gauge needles. Fifty healthy children were divided according to age into Group I (N = 25; 4-5 years) and Group II (N = 25; 5-6 years). Each group was further subdivided according to the needle gauge as follows: Group IA (26 gauge), Group IB (31 gauge), Group IIA (26 gauge), and Group IIB (31 gauge). Using a lottery method, the gauge of the needle to be used at the first visit for local anesthesia administration was selected. Children's reactions to pain were evaluated using a Modified Behavioral Pain Scale. Immediately after administration of local anesthesia, pain perception was evaluated using the Faces pain rating scale. In the subsequent visit, another needle gauge was used to administer local anesthesia, and the previously described evaluations were performed. At the third appointment, the child was shown both syringes and asked to choose one of the syringes they preferred, and the choice was noted. When local anesthesia was administered using a 31-gauge needle, pain perception was similar between the two groups. In group II, the children demonstrated significantly higher arm and leg movements (P = 0.001). However, the difference was significant in group I alone (P < 0.001). Irrespective of age, anesthesia with a 31-gauge needle resulted in significantly lower pain perception than anesthesia with a 26-gauge needle.